Pengaruh Rasio Keuangan dan Ukuran Perusahaan Terhadap Return Saham Dengan Corporate Social Responsibility Sebagai Variabel Intervening Pada Perusahaan Idx-30 Yang Terdaftar Di Bei Pada Masa Pandemi Covid-19 (2019-2021) - Nuryani, Tiya; Kamal, Al Haq; Syah, Toufan Aldian (DAS Institute, 2023)
The purpose of this study was to examine the effect of financial ratios and company size on stock returns with Corporate Social Responsibility as an intervening variable in IDX-30 companies listed at the IDX During the covid-19 pandemic (2019-2021). This study uses quantitative methods with secondary data in the form of annual financial reports and sustainability reports on IDX-30 companies listed on the IDX for the 2019-2021 period. The data analysis technique in this study used SPSS version 26 to test the data and used the Sobel Test Calculator for the Significance of Mediation to calculate the Sobel Test online. With the results obtained that ROA, CR, and Company Size have a significant negative effect on stock returns, DER has no significant effect on stock returns and CSR has a significant positive effect on stock returns. CSR is proven to be an intervening variable between ROA, CR, and company size variables on stock returns. However, it cannot be an intervening variable for the DER variable on stock returns.